2015
DOI: 10.1071/ch15340
|View full text |Cite
|
Sign up to set email alerts
|

The Palladium-Catalysed Intramolecular Alder-ene (IMAE) Reactions of Certain Heteroatom-Linked 1,6-Enynes: The Formation of Hexahydro-Indoles and -Benzofurans

Abstract: A short review of the literature on palladium-catalysed intramolecular Alder-ene reactions of C-, N-, and O-linked 1,6-enynes is provided with a particular focus on the use of the latter two processes in the authors' laboratories for the purposes of constructing various alkaloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…We have reported that the Pd­(II)-catalyzed intramolecular Alder-ene (IMAE) reaction of propargylated 1-amino-2-aryl-2-cyclohexenes allows for the ready generation of C3a-arylated hexahydroindoles and subsequently deployed this and closely related processes in the synthesis of a range of natural products and natural product scaffolds . Accordingly, we sought to use such a process for preparing compounds related to compound 3 (Figure ) in order to further probe the validity of the proposed biogenesis of the gracilamine framework.…”
supporting
confidence: 66%
“…We have reported that the Pd­(II)-catalyzed intramolecular Alder-ene (IMAE) reaction of propargylated 1-amino-2-aryl-2-cyclohexenes allows for the ready generation of C3a-arylated hexahydroindoles and subsequently deployed this and closely related processes in the synthesis of a range of natural products and natural product scaffolds . Accordingly, we sought to use such a process for preparing compounds related to compound 3 (Figure ) in order to further probe the validity of the proposed biogenesis of the gracilamine framework.…”
supporting
confidence: 66%
“…Thus, Suzuki–Miyaura cross-coupling of the known boronate ester 3 with the previously reported cycloalkenyl bromide 4 gave the arylated cyclohexene 5 (83%), and this was readily propargylated at nitrogen using 1-bromo-2-butyne in the presence of sodium hydride to give derivative 6 in 91% yield. This last compound participated in an intramolecular Alder-ene (IMAE) reaction, using Pd­(OAc) 2 and the strong σ-donating ligand N , N ′-bis­(benzyli­dene)­ethylene­diamine (BBEDA) in refluxing toluene, thereby affording the C3a-arylated hexahydroindole 7 in 73% yield. This IMAE product was accompanied by small amounts of uncharacterized materials, one of which is likely to the isomeric cyclopropyl-containing system analogous to that observed when the tosyl analogue of substrate 6 was engaged in the same type of reaction.…”
Section: Resultsmentioning
confidence: 99%
“…3H), 1.54 (s, 1H), 0.92 (s, 9H), 0.14 (s, 3H), 0.13 (s, 3H); 13 C NMR (100 MHz, CDCl 3 ) δ 169.7, 147.9, 147.4, 145.9, 141.9, 137.9, 132.9, 132.4, 132. (3R,4aS,5S,11bR,Z)-rel-3-((tert-Butyldimethylsilyl)oxy)-12ethylidene-4,4a-dihydro-3H,6H-5,11b-ethano [1,3]dioxolo[4,5j]phenanthridin-6-one (8). A magnetically stirred solution of compound 7 (224 mg, 0.35 mmol, 1.0 equiv) in dry DMF (10 mL) containing cesium carbonate (516 mg, 1.58 mmol, 4.5 equiv) and pchlorothiophenol (211 mg, 1.46 mmol, 4.2 equiv) was stirred at 22 °C for 1 h then quenched with NH 4 Cl (10 mL of a saturated aqueous solution) and extracted with dichloromethane (3 × 20 mL).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…For instance, in 1985, Trost reported the first example of palladium-catalyzed IMAE reactions of 1,6-enynes under mild conditions (Figure b) . Followed by this seminal work, IMAE reactions promoted by Pd catalysts as well as other transition metal catalysts have been widely studied and achieved much progress, providing facile access to structurally diversified molecules . Very recently, Banwell reported a palladium-catalyzed and triethylsilyl group-regulated IMAE reaction of O- and N-linked 1,6-enynes (Figure c) .…”
mentioning
confidence: 99%